Synthesis and Antimicrobial Evaluation of Some New Benzoxazinone and Quinazolinone Derivatives - M.G., Assy; A.A., Abdalha; A.E, Abdel Aziz (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Ring opening reactions of benzoxazinone (2) with nitrogen and oxygen nucleophiles gave the corresponding benzamides (3)&(4) and benzoates (5).Quinazolinone derivatives (6) and (7) were obtained upon treatment of (2) with hydrazine hydrate and/or hydroxylamine hydrochloride.Triazole derivatives (8a â€“ b) were obtained when (2) was subjected to react with semicarbazide and/or thiosemicarbazide respectively. Reaction of (2) with sodium azide gave a mixture of tetrazole derivative (9) and benzoimidazolone derivative (10). The antimicrobial activity ofÂ some synthesized compounds was examined against bacteria, fungi and yeast. Some of the tested compounds showed promising activities.